2018
DOI: 10.1159/000494800
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto Encephalopathy as a Complication of Autoimmune Thyroiditis

Abstract: Objective: To present a case of Hashimoto encephalopathy as a complication of autoimmune thyroiditis. Clinical Presentation and Intervention: A previously healthy 56-year-old female presented with rapidly progressive cognitive decline and visual hallucinations. Being a diagnosis of exclusion, Hashimoto encephalopathy required an extensive laboratory and diagnostic workup, which was done over the course of a 15-day hospitalization. The patient recovered after initial treatment with intravenous methylprednisolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…6,9 Recently, Blanchin et al reported that TPOAb from HE patients could bind cerebellar astrocytes in HE patients but not in Hashimoto thyroiditis patients. 11,12 This may support the role of TPOAb in the pathogenesis of HE. In addition, the titre of thyroidantibodies does not correlate with severity or improvement neurological illness.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…6,9 Recently, Blanchin et al reported that TPOAb from HE patients could bind cerebellar astrocytes in HE patients but not in Hashimoto thyroiditis patients. 11,12 This may support the role of TPOAb in the pathogenesis of HE. In addition, the titre of thyroidantibodies does not correlate with severity or improvement neurological illness.…”
Section: Discussionsupporting
confidence: 53%
“…2,3,10,14 Brain MRI may show abnormalities such as cerebral atrophy, focal cortical abnormality, diffuse subcortical abnormality and nonspecific subcortical focal white matter abnormality. 3,12,14 In our patient the diagnosis of HE was made by the noted high serum thyroid peroxidase antibodies, slow background diffusion of waves shown by EEG, positive neurological symptoms, normal MRI, after excluding all other potential causes. Steroid is the first line therapeutic choice, proved to be the most successful and effective treatment method for HE.…”
Section: Discussionmentioning
confidence: 80%
“…The clinical features are various, with a wide spectrum ranging from weakness to severe psychiatric disorders (Fiore et al, 2019; Netuluri et al, 2018). To the best of the authors’ knowledge, this is the first reported case of HE with hypochondriacal delusions as a sole manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may experience excessive irrita-bility or heaviness, sleep disorders, anxiety, and depression [1,3,6]. Myopathy, neuropathy, ataxia, and encephalopathy are often diagnosed with them [2,7]. The cause of these symptoms has not yet been identified, and the pathomechanism of these changes is still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, attention has been paid to the impact of hormone-compensated autoimmune thyroiditis on CNS function and the possibility of developing severe neurological complications in euthyroid patients. The severest of these is Hashimoto encephalopathy (EH) or SREAT (S-steroid responsive, E-encephalopathy, A-associated, T-autoimmune thyroiditis) [3,[7][8][9][10]. The causes of these disorders are unknown.…”
Section: Introductionmentioning
confidence: 99%